Evaluation of prognosis of acute colangitis patients via hematological parameters - Zubeyr Said Agac; Selma Karaahmetoglu; Taner Akyol (Medicine Science, 2023)
Early differentiation of cases with severe acute cholangitis is important for optimal treatment. In this study, it was aimed to elucidate the prognosis with complete blood count parameters among patients with acute cholangitis. Clinical and laboratory findings of 200 patients with acute cholangitis at Ankara City Hospital between February 2019 and October 2019 were retrospectively analyzed. Neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, red cell distribution width and mean platelet volume levels were recorded from blood analysis at the time of admission. According to Tokyo guidelines, patients were divided into 3 groups as mild, moderate and severe acute cholangitis. In order to evaluate the prognosis, the length of hospital stay, the status of hospitalization in the medical intensive care unit and blood culture growth were investigated with hematological parameters. Of the 200 patients, 109 (54.5%) were male and 91 (45.5%) were female. According to Tokyo criteria, 17 patients' status was evaluated as severe, 70 as moderate and 113 as mild acute cholangitis. The area under the receiver operating characteristics curve for neutrophil-lymphocyte ratio measurements was statistically significant in distinguishing the mild vs moderate disease (AUC=0.694; 95% Confidence Interval (CI):0.586-0.802 and p=0.008), with a diagnostic accuracy rate of 59.5%. The diagnostic accuracy rate of red cell distribution width (AUC=0.603; 95% CI: 0.523-0.683 and p=0.013) was 61.5% and the diagnostic accuracy rate of mean platelet volume (AUC=0.582 95% CI: 0.502-0.662 and p=0.047) was 57.5% achieving a statistical significance. Neutrophil-lymphocyte ratio, red cell distribution width and mean platelet volume analysis is routinely obtained from complete blood count almost in every patient. These are inexpensive and easily accessible diagnostic markers and thus, might be useful in the differentiation of mild and severe acute cholangitis patients and their prognosis. [Med-Science 2023; 12(3.000): 641-6]